Fundoscopy in the smartphone age: current ophthalmoscopy methods in neurology - Richard Henrik Corr (Arquivos de Neuro-Psiquiatria, 2023)
The observation of the human retina in vivo began in 1851 after the invention of the first ophthalmoscope by the German physicist Hermann von Helmholtz. In the following decades, direct and indirect ophthalmoscopy, with the use of ophthalmoscopes and condensing lenses, respectively, became part of the clinical examination, especially in ophthalmology and neurology. Today, over 170 years later, many ophthalmoscopes and condensing lenses exist on the market. Nevertheless, ophthalmoscopy is still not widely adopted as part of the physical exam of general practitioners, and the teaching of ophthalmoscopy in medical school remains challenging. Studies have shown that students prefer using newer ophthalmoscope models or condensing lenses during training, but most do not feel confident in performing ophthalmoscopy afterwards, regardless of the models used. Also, few students acquire ophthalmoscopes for their future practice, and clinical trials have not clearly demonstrated superiority of newer ophthalmoscope models over the conventional ones in diagnostic accuracy. The technological improvement of smartphone cameras in recent years has made it feasible to photograph the fundus of the eye using ophthalmoscopes or condensing lenses, reducing the need for retinographs and similar equipment. Smartphone assisted indirect fundoscopy is becoming increasingly popular. This approach allows adequate identification of the structures of the fundus, is cost-efficient, easy to implement, and permits easy recording and sharing of the images obtained, which is useful for case discussions and medical teaching. However, controlled clinical trials validating this method in the evaluation of optic nerve pathologies are needed.